Performance of body fat and body mass index cutoffs in elevated blood pressure screening among male children and adolescents - Fernandes, Romulo A. [UNESP]; Christofaro, Diego G. D.; Buonani, Camila [UNESP]; Monteriro, Henrique L. [UNESP]; Cardoso, Jefferson R.; Freitas, Ismael F. [UNESP]; Machado, Dalmo R. L. (Nature Publishing Group, 2011)
For percentage of body fat (%BF), there are no internationally accepted cutoffs. The primary function of body fat cutoffs should be to identify not only excessive body fatness, but also the increased risk of unhealthy outcomes, such as hypertension. The purpose of this study was to analyze the accuracy of different %BF and body mass index (BMI) cutoffs as screening measures for EBP in pediatric populations. It was a cross-sectional study with a sample of 358 male subjects from 8 to 18 years old. BP was measured by the oscilometric method, and body composition was measured by dual-energy X-ray absorptiometry (DXA). The accuracy of three reference tables used for body fat cutoffs was assessed. The three body fat reference tables were highly specific, but insensitive, for elevated BP screening. For elevated BP screening, all body fat cutoffs presented similar sensitivity (range=48.3-53.7%) and specificity (range=79.2-84.1%). The body fat cutoffs performed no better than BMI in screening of children and adolescents at risk of elevated BP (EBP). BMI seems a more attractive tool for this function, as it performed similarly and can be applied in large surveys and with lower costs. Hypertension Research (2011) 34, 963-967; doi:10.1038/hr.2011.61; published online 26 May 2011
Keywords: adolescent; children; dual-energy X-ray absorptiometry; obesity; receiver operating characteristic curve